2019
DOI: 10.1002/chem.201904169
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Functionalization of Helicenes

Abstract: Herein, a visible‐light photochemical approach for practical helicene functionalization at very mild reaction conditions is described. The photochemical reactions allow for the regiospecific and innate late‐stage functionalization of helicenes and are easily executed either through the activation of C(sp2)−Br bonds in helicenes using K2CO3 as inorganic base or direct C(sp2)−H helicene bond functionalization under oxidative photoredox reaction conditions. Overall, using these transformations six different funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The photochemical reaction protocols permits the regiospecific and classic late‐stage functionalization of helicenes that can be effortlessly brought about either through the activation of C(sp 2 )−Br bonds in helicenes utilizing K 2 CO 3 as inorganic base or direct C(sp 2 )−H helicene bond functionalization by means of oxidative photoredox conditions (Scheme 171). [189] …”
Section: Photochemical Methods Of C−h Functionalizationmentioning
confidence: 99%
“…The photochemical reaction protocols permits the regiospecific and classic late‐stage functionalization of helicenes that can be effortlessly brought about either through the activation of C(sp 2 )−Br bonds in helicenes utilizing K 2 CO 3 as inorganic base or direct C(sp 2 )−H helicene bond functionalization by means of oxidative photoredox conditions (Scheme 171). [189] …”
Section: Photochemical Methods Of C−h Functionalizationmentioning
confidence: 99%
“…Storch and König studied both reductive and oxidative light-induced transformations of helicene derivatives . They showed that bromohelicenes can generate helicenyl radicals upon irradiation with blue light in the presence of potassium carbonate in DMSO (Scheme A, transformations of 9-bromo[7]­helicene ( 55 ) are shown as representative examples).…”
Section: Transformation Of Reactive Functional Groupsmentioning
confidence: 99%
“…Storch and Konig studied both reductive and oxidative lightinduced transformations of helicene derivatives. 44 They showed that bromohelicenes can generate helicenyl radicals upon irradiation with blue light in the presence of potassium carbonate in DMSO (Scheme 11A, transformations of 9bromo [7]helicene (55) are shown as representative examples). This species can be subsequently reacted with a suitable trapping agent, ranging from various heterocycles (pyrrole, thiophene, furan, indole) to heteroatomic compounds, such as triethyl phosphite, dimethyldisulfide, or bis(pinacolato)diboron.…”
Section: Transformation Of Reactive Functionalmentioning
confidence: 99%
“…78 Non-C-H photocatalyzed phosphinylation systems that involve a carbon radical species have also been reported in the literature, such as the phosphonylation of aryl halides/triflates, 79 arylazosulfones, 80 benzotriazoles 81 or bromo [6]helicenes. 82 In pioneering work, Barton, in 1993, used a photogenerated carbon radical to attack directly white phosphorus and obtained phosphonic acids in good yields after oxidative work-up. 83…”
Section: Review Synthesismentioning
confidence: 99%